The G-Protein-Coupled Long-Chain Fatty Acid Receptor GPR40 and Glucose Metabolism - Tomita, Tsutomu; Hosoda, Kiminori; Fujikura, Junji; Inagaki, Nobuya; Nakao, Kazuwa (Frontiers in Endocrinology, 2014)
Free fatty acids (FFAs) play a pivotal role in metabolic control and cell signaling processes in various tissues. In particular, FFAs are known to augment glucose-stimulated insulin secretion (GSIS) by pancreatic beta cells, where fatty acid-derived metabolites, such as long chain fatty acyl-CoAs, are believed to act as crucial effectors. Recently, G-protein-coupled receptor 40 (GPR40), a receptor for long-chain fatty acids, was reported to be highly expressed in pancreatic beta cells and involved in the regulation of insulin secretion. Hence, GPR40 is considered to be a potential therapeutic target for the treatment of diabetes. In this review, we summarize the identification and gene expression patterns of GPR40 and its role in glucose metabolism. We also discuss the potential application of GPR40 as a therapeutic target.